Expression of vimentin and glial fibrillary acidic protein in human developing spinal cord - Lukás, Z; Dráber, P; Bucek, J; Dráberová, E; Viklický, V; Stasková, Z (The Histochemical journal, 1989)
Expression of intermediate filament proteins was studied in human developing spinal cord using immunoperoxidase and double-label immunofluorescence methods with monoclonal antibodies to vimentin and glial fibrillary acidic protein (GFAP). Vimentin was found in the processes of radial glial cells in 6-week embryos, while GFAP appeared in vimentin-positive astroglial cells at 8-10 weeks. GFAP and vimentin were present in approximately equal amounts in differentiating astrocytes in 23-week spinal cord. In 30-week fetuses, astrocytes reacted strongly for GFAP, while both the reaction intensity and the number of vimentin-positive cells fluctuated predominantly in the grey matter. No clear-cut transition from vimentin to GFAP was noticed during the development of astrocytes. The majority of ependymal cells in 23-week fetuses contained vimentin but only a few of them reacted for GFAP. The expression of vimentin continued during the whole development of the ependymal layer, in contrast to the reactivity for GFAP which disappeared between the 30th week and term.
Keywords: Electrophoresis, Polyacrylamide Gel; fluorescenční protilátková technika; Microscopy, Fluorescence; exprese genu; Pregnancy; Humans; Glial Fibrillary Acidic Protein; elektroforéza v polyakrylamidovém gelu; Gene Expression; Spinal Cord; gestační stáří; Antibodies, Monoclonal; fluorescenční mikroskopie; Female; mícha; gliový fibrilární kyselý protein; lidé; Vimentin; barvení a značení; ženské pohlaví; těhotenství; monoklonální protilátky; Fluorescent Antibody Technique; Staining and Labeling; Gestational Age; vimentin